hBN nanoparticle-assisted rapid thermal cycling for the detection of acanthamoeba - Rasheed, Abdul Khaliq; Siddiqui, Ruqaiyyah; Mohammed Kabir Ahmed, Salma; Gabriel, Shobana; Jalal, Mohammed Zayan; John, Akbar; Ahmed Khan, Naveed (MDPI, 2020)
Acanthamoeba are widely distributed in the environment and are known to cause blinding keratitis and brain infections with greater than 90% mortality rate. Currently, polymerase chain reaction (PCR) is a highly sensitive and promising technique in Acanthamoeba detection. Remarkably, the rate of heating–cooling and convective heat transfer of the PCR tube is limited by low thermal conductivity of the reagents mixture. The addition of nanoparticles to the reaction has been an interesting approach that could augment the thermal conductivity of the mixture and subsequently enhance heat transfer through the PCR tube. Here, we have developed hexagonal boron nitride (hBN) nanoparticle-based PCR assay for the rapid detection of Acanthamoeba to amplify DNA from low amoeba cell density. As low as 1 × 10 −4 wt % was determined as the optimum concentration of hBN nanoparticles, which increased Acanthamoeba DNA yield up to ~16%. Further, it was able to reduce PCR temperature that led to a ~2.0-fold increase in Acanthamoeba DNA yield at an improved PCR specificity at 46.2 °C low annealing temperature. hBN nanoparticles further reduced standard PCR step time by 10 min and cycles by eight; thus, enhancing Acanthamoeba detection rapidly. Enhancement of Acanthamoeba PCR DNA yield is possibly due to the high adsorption affinity of hBN nanoparticles to purine (Guanine—G) due to the higher thermal conductivity achieved in the PCR mixture due to the addition of hBN. Although further research is needed to demonstrate these findings in clinical application, we propose that the interfacial layers, Brownian motion, and percolation network contribute to the enhanced thermal conductivity effect